answersLogoWhite

0


Best Answer

6 + w - 2w - 11 + 6w = -5 + 5w

User Avatar

Wiki User

โˆ™ 2016-12-03 22:51:58
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides
๐Ÿ““
See all Study Guides
โœ๏ธ
Create a Study Guide

Add your answer:

Earn +20 pts
Q: What is 6 plus w-2w-11 plus 6w?
Write your answer...
Submit
Related questions

What is the factor for 6w plus 18?

6(w + 3)


6w is less than or equal to 36?

It depends on the value of w. w < 6 then 6w < 36 w = 6 then 6w = 36 and w > 6 then 6w >36


What is 4w plus 8 plus 6w-4?

It is 10w + 4.


What is 6x-6w in simplest form?

12


What is equivalent to 6w plus 5 - 3w plus 7?

3w + 12


What is 4w plus 2w-2?

It is: 6w-2


What is the sum of 7w - 4w - 6w?

7w - 4w - 6w = (7 - 4 - 6)w = -3w


If 6w equals 32 and w must equal decimal?

If 6w = 32, w = 32/6 = 5.333


What is 5 plus 6w-2w?

It is: 5+4w simplified


Which is another way to write w plus w plus w plus w plus w plus w?

6w


What are the coefficients of 2w-6w plus 9?

2w-6w+9 -4w+9 the coefficient of -4w is -4


What is 7x-6w?

7x-6w = 1


Subtract 8 from 6 times w?

6w - 8


Which phrase describes the variable expression 6 times w?

6w


What is a 6-4 record percentage?

6w 4l --> 6 / (6+4) x 100 = 60%


If 16-7w plus 14-6w what is the value of w-1?

"16-7w plus 14-6w" is an algebraic expression - not an equation nor an inequality. It cannot be solved. So there is no way to determine the value of w and therefore the value of w-1.


What is 16 equals 4 w plus 2 w minus 2?

Write out the equation: 16 = 4w + 2w - 2 Collect like terms (terms without w and terms with w): 16 = 6w - 2 Put all the terms without w on the same side (add 2 to both sides): 16 + 2 = 6w - 2 + 2 18 = 6w Get rid of the coefficient (divide by 6): 18 / 6 = 6w / 6 3 = w


What is w if 29 plus 6w equals 11w plus 4?

29 + 6w = 11w + 425 = 5w5 = ww = 5


6w 0.144 what is the answer?

If you mean: 6w = 0.144 then w = 0.24


6W of H the E?

6 wives of Henry the Eighth


What does 2w-11 plus 4w equals 7?

It is an equation and the value of w is 3 2w - 11 + 4w = 7 6w - 11 = 7 6w = 7 + 11 6w = 18 w = 3


What is the factor of 5w squared minus negative 6w plus 1?

(5w + 1)(w + 1)


How do you solve 2w plus 16 equals -6w minus 8?

2w + 16 = - 6w - 8 2w + 16 + 6w = - 8 8w + 16 = - 8 8w = - 8 - 16 8w = - 24 w = - 3


Factor the following problem 36w2 - 25z2?

(6w - 5z)(6w + 5z)


Completely factor this problem 36w2-25z2?

(6w + 5z)(6w - 5z)